Monitoring and Evaluation of Smoke Free Policy in Medan City: Case Study of Medan City - Putra Apriadi Siregar (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
A smoke-free policy (SFP) has existed since 2014; after seven years of implementing smoke-free policy (SFP), it turns out that the implementation of the policy is not implemented properly where there are still many smokers, there are cigarette advertisements in SFP, butts are also still often found. This study aims to find out how the smoke-free policy (SFP) works in Medan City.. This study uses a cross-sectional study with a quantitative approach. The objects in this study are 160 places categorized as SFP based on regulations in the city of Medan. Data were collected by observing the SFP checklist. The results of this study indicate that there is still the smell of cigarette smoke in the SFP building in 19 (11%) places. There are still 64 smoking-free areas found by visitors who smoke around the SFP building. There are still cigarette advertisements in the SFP in 9 places, cigarette sellers in 28 places, and cigarette butts are still found in 41 places. The results of this study showed that the most violations of the smoking-free area policy occurred in child play station facilities (30.7%), public facilities (38.8%) and workplaces (50%). The smoking-free policy was most adhered to by health facilities (75%) and educational facilities (56%). The smoke-free policy (SFP) in Medan City has not implemented the concept of an SFP, especially related to the prohibition on cigarette advertising which has not been completely implemented, the ban on cigarette advertising at the SFP location has only been implemented in educational institutions and offices, such as banks and plazas.